Effect of Foot Exercise and Care on Peripheral Vascular Status in Patients with Diabetes Mellitus - Selpina Embuai; Hani Tuasikal; Moomina Siauta (Universitas Airlangga, 2019)
Introduction: Diabetes mellitus is a cause of health problems which occurs in most countries. Approximately 13 - 15% of all patients with diabetes mellitus will experience peripheral circulatory disorders. Foot exercise and foot care are interventions that can be implemented to prevent foot ulcers.Methods: This study employed a pre-post-test quasi-experimental design with a control group. The sample consisted of 94 patients with diabetes mellitus who were assigned to the intervention group (n=47) and the control group (n=47) respectively. Consecutive sampling was used to recruit the samples. The instruments used to collect the data included 10-g monofilament for the diabetic neuropathy test, a HbA1c test and a sphygmomanometer. The collected data was analyzed using a paired t-test.Results: The results of this study showed there to be significant effects from foot exercise and foot care on the HbA1c test, in relation to the frequency of the dorsalis pedis artery and diabetic neuropathy with a significance value of 0.00 (p<0.05). However, in the ankle-brachial index measurement, there were no significant differences between the intervention and control groups with a significance value of 0.26 (p>0.05).Conclusion: Foot exercise and foot care can be one of the independent nursing interventions used to prevent the complications of diabetes mellitus, as they have been proven to improve the peripheral vascular status of patients with diabetes mellitus by 70-80%.